Antimicrobial peptide pleurocidin synergizes with antibiotics through hydroxyl radical formation and membrane damage, and exerts antibiofilm activity - Choi, Hyemin; Lee, Dong Gun (Biochimica et biophysica acta, 2012)
Pleurocidin, a 25-mer antimicrobial peptide (AMP), is known to exert bactericidal activity. However, the synergistic activity and mechanism(s) of pleurocidin in combination with conventional antibiotics, and the antibiofilm effect of the peptide are poorly understood. The interaction between pleurocidin and antibiotics was evaluated using checkerboard assay. To study the mechanism(s) involved in their synergism, we detected hydroxyl radical formation using 3′-(p-hydroxyphenyl) fluorescein, measured the NAD+/NADH ratio by NAD+ cycling assay, observed change in bacterial viability with the hydroxyl radical scavenger thiourea, and investigated cytoplasmic membrane damage using propidium iodide. Also, the antibiofilm effect of pleurocidin was examined with the tissue culture plate method. All combinations of pleurocidin and antibiotics showed synergistic interaction against bacterial strains (fractional inhibitory concentration index (FICI)≤0.5) except for Enterococcus faecium treated with a combination of the peptide and ampicillin (FICI=0.75). We identified that pleurocidin alone and in combinations with antibiotics induced formation of hydroxyl radicals. The oxidative stress was caused by a transient NADH depletion and the addition of thiourea prevented bacterial death, especially in the case of the combined treatment of pleurocidin and ampicillin showing synergisms. The combination of pleurocidin and erythromycin increased permeability of bacterial cytoplasmic membrane. Additionally, pleurocidin exhibited a potent inhibitory effect on preformed biofilm of bacterial organisms. In conclusion, pleurocidin synergized with antibiotics through hydroxyl radical formation and membrane-active mechanism, and exerted antibiofilm activity. The synergistic effect between pleurocidin and antibiotics suggests the AMP is a potential therapeutic agent and adjuvant for antimicrobial chemotherapy. ► We aimed to evaluate the combination effect of pleurocidin with antibiotics. ► Most combinations between pleurocidin and antibiotics showed synergistic effects. ► We investigated the mechanism(s) involved in the synergistic effects. ► The synergisms were induced by hydroxyl radical production and membrane damage. ► Additionally, we indentified that pleurocidin exerted antibiofilm effect.